A comparison between transient CFD and FEM simulations of solar central receiver tubes using molten salt and liquid metals. (October 2017) - Fritsch, Andreas; Uhlig, Ralf; Marocco, Luca; Frantz, Cathy; Flesch, Robert; Hoffschmidt, Bernhard
Highlights: Comparison between thermal receiver models on different levels of detail (1D, 2D and 3D-simulation). Examination of steady state and transient model behaviour. Analysis of different heat transfer fluids: molten salt (represents high Prandtl number fluids) and liquid metals (low Prandtl number fluids). Model validation with experimental data of the Solar Two receiver. Abstract: The design of central receivers in solar thermal power plants is crucial for efficiency and operating behavior of the plant. The local heat flux distribution on the absorber tubes varies, depending on time, weather conditions and aim point strategy. A proper receiver design needs accurate thermodynamic models to detect local temperature distribution, especially hot spots on the absorber tubes. Moreover, due to highly transient boundary conditions, the dynamic behavior of the model is important. Starting with a detailed CFD model of a single receiver tube several simplified FEM models were investigated. The influence of an inhomogeneous heat flux distribution on the absorber and the dynamic behavior after a sudden change of heat flux (e.g. due to passage of clouds) were analyzed. In order to consider radiation exchange between surfaces, simulations with a whole receiver panel were also conducted. The FEM model with one-dimensional fluid elements and constant heat transfer coefficients shows a very good agreement with the detailed CFD model. Further simplifications like the presented model, where the tubes are discretized as projected surfaces are computationally very efficient and can be used for relative comparison between receiver configurations. However, this simplification has deviations in the prediction of tube temperatures and radiation losses. Finally, the receiver simulation of the Solar Two power plant validates the FEM model with the measured data for solar salt. The investigation of liquid metals considers a single tube with an inhomogeneous heat flux on its surface. The detailed analysis shows, that the Nusselt number correlation plays an important role for the tube wall temperature. If the Nusselt number is overestimated in the region of the peak heat flux, the simplified model results in a lower tube wall temperature.